2023
DOI: 10.3389/fimmu.2023.1115548
|View full text |Cite
|
Sign up to set email alerts
|

Isolated anti-Ro52 identifies a severe subset of Sjögren’s syndrome patients

Abstract: IntroductionSerum autoantibodies targeting the SSA/Ro proteins are a key component of the classification criteria for the diagnosis of Sjögren’s syndrome (SS). Most patients' serum reacts with both Ro60 and Ro52 proteins. Here we compare the molecular and clinical characteristics of patients diagnosed with SS with anti-Ro52 in the presence or absence of anti-Ro60/La autoantibodies.MethodsA cross-sectional study was performed. Patients in the SS biobank at Westmead Hospital (Sydney, Australia) that were positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(49 reference statements)
0
4
0
Order By: Relevance
“… 24 25 Although isolated anti-Ro52 SS patients have rarely been studied, a recent study found that patients with isolated anti-Ro52 (which was initially the case for our patient) may represent a severe subset of SS patients with higher disease activity over patients with additional autoantibodies. 26 Among seropositive SS patients, those with isolated anti-Ro52 are rarer (around 11%) compared with those with anti-Ro60 and/or anti-La. Anti-Ro52 autoantibodies are found in a range of autoimmune diseases (38% in a diagnostic laboratory cohort) and non-autoimmune diseases such as malignancies and interstitial lung disease (ILD).…”
Section: Discussionmentioning
confidence: 99%
“… 24 25 Although isolated anti-Ro52 SS patients have rarely been studied, a recent study found that patients with isolated anti-Ro52 (which was initially the case for our patient) may represent a severe subset of SS patients with higher disease activity over patients with additional autoantibodies. 26 Among seropositive SS patients, those with isolated anti-Ro52 are rarer (around 11%) compared with those with anti-Ro60 and/or anti-La. Anti-Ro52 autoantibodies are found in a range of autoimmune diseases (38% in a diagnostic laboratory cohort) and non-autoimmune diseases such as malignancies and interstitial lung disease (ILD).…”
Section: Discussionmentioning
confidence: 99%
“…[ 69 ] More clinical profile has shown that the higher levels of IgG1 and IgA SLE patients related to B‐cell abnormalities and type I IFN overproduction in SLE patients, [ 47 ] indicating Ro52/TRIM21 may induce immunoglobulins in pathogenesis and contribute to the severity of disease. It has also been demonstrated in many studies that a higher level of anti‐Ro52/TRIM21 Ab related to severe symptoms on SLE, [ 152 ] SS, [ 153–156 ] juvenile myositis [ 145 ] antisynthetase syndrome, [ 157 ] dermatomyositis, [ 158 ] and thereby anti‐Ro52/TRIM21 Ab's role on the progress of TRIM21‐related autoimmune diseases. Albeit anti‐Ro52/TRIM21 IgG is one of the most common autoantibodies in diseases and widely employed in research for its high affinity as described in Section 3.…”
Section: Trim21 In Autoimmune Diseasesmentioning
confidence: 99%
“…However, A recent study on Anti‐Ro52/TRIM21 serology found no differences for anti‐Ro52 antibody titres between all subsets by ELISA (IgA, IgM and IgG isotypes) or LIA densitometry (IgG isotype) in Sjögren's syndrome. [ 156 ] And the specific anti‐Ro52 antibody isotypes were less discussed in literature. Overall, clinical data regarding anti‐Ro52/TRIM21 antibodies and their implications remain more controversial and less clear.…”
Section: Trim21 In Autoimmune Diseasesmentioning
confidence: 99%
“…Hence, the proportion of patients with seronegative SS varies in the literature, ranging from 8% to 37% of SS cohorts. [5][6][7] Because of the lack of SS-associated autoantibody biomarkers, seronegative SS may be missed in the clinic if further investigations such as an MSGB are not performed. It is important to differentiate patients with seronegative SS from other patients who have sicca symptoms due to the potential for serious extraglandular manifestations in the former.…”
Section: Editorialmentioning
confidence: 99%